Perancangan Strategi Pemasaran 4c Menggunakan Google My Business Dengan Analisis SWOT Pada UMKM Warung Nasi - Aini, Feby Nur; Jaya, Rama Chandra (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This aims to examine and analyze the factors influencing the company and to design a 4C Marketing Strategy using Google My Business with a SWOT analysis for Warung Nasi Ibu Iiis. SWOT analysis method, this research examines the internal factors (Strengths and Weaknesses) and external factors (Opportunities and Threats) that affect the business. Based on this analysis, an effective and efficient strategy utilizing Google My Business is implemented as marketing for Warung Nasi Ibu Iis, expanding the market for the business. Additionally, the results of using Google My Business are expected to enhance Warung Nasi Ibu Iis's product sales